(untitled) (Al-Qamar, 2025)
This article explores the concept, significance, and linguistic richness of supplication (du’a) in Islam. Derived from the Arabic root "د ع و," du’a signifies a profound act of seeking and longing towards Allah, reflecting submission and reliance. Through an analytical approach, the study highlights the essential role of supplication in the Quran and Hadith, emphasizing its multifaceted meanings such as worship, request, and invocation. Examples include Quranic verses like "Call upon Me, and I will respond to you," and prophetic sayings such as "Supplication is the essence of worship."The discussion extends to the eloquence in the supplications of Imam Zain al-Abidin, showcasing his mastery in rhetorical devices such as command, negation, and exclamation. His supplications are a testament to the intersection of devotion and linguistic sophistication. Key themes include the transformative power of du’a in achieving closeness to Allah, seeking divine mercy, and warding off calamities.This article integrates theological insights with linguistic analysis, presenting du’a as a spiritual lifeline and a profound act of communication with the Divine. Through the eloquence of Imam Zain al-Abidin’s prayers, readers are invited to appreciate the spiritual and rhetorical depth of this pivotal Islamic practice.